The delivery of Cultural Ecosystem Services in urban forests of different landscape features and land use contexts - Yuan Wang; Jari Niemelä; D. Johan Kotze (People and Nature, 2022)
Abstract Urban greenspace provides citizens with important cultural ecosystem services (CES). Identifying landscape features and land use contexts that facilitate CES delivery is critical for guiding urban greenspace management. However, how landscape features and urban context interact with each other in influencing the CES of greenspaces remains unclear. Studies on the CES of patchy urban forests are needed as they are essential urban CES providers, but vulnerable under urban land use pressure. To address these concerns, we compared the CES of 20 urban forest patches in Helsinki, Finland, with five different combinations of landscape features (i.e. size and connectivity) and land use contexts (i.e. surrounding construction density). CES were assessed through an on‐site survey on visitors' use, perceptions of CES experience and overall satisfaction, to capture the possible disparities among CES measurements. In larger (>20 ha) forests, visitors were highly satisfied with CES, particularly appreciating the experience of physical health improvement and inspiration through longer and more intense physical uses. Visitors of urban forests in a low construction density context appreciated experiences of cultural heritage, psychological restoration and physical health improvement. Urban forests deliver unique CES characterised by physical use and the benefit of restoration, aesthetics and contact with nature. We suggest that maintaining large urban forests is more effective in promoting CES in high‐density areas. In low‐density areas, maintaining small forests with open greenspace in the surroundings can also promote CES experiences. We identify management gaps caused by a mismatch between use intensity and CES experiences of urban forests, while both are important in determining people's overall satisfaction. Read the free Plain Language Summary for this article on the Journal blog.